Analisis Pengaruh Penyekatan Kanal Terhadap Pembasahan Di Lahan Gambut (Studi Kasus: Desa Lukun, Kecamatan Tebing Tinggi Timur, Kabupaten Kepulauan Meranti) - Rahmayati Aprillia Putri; Rinaldi Rinaldi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One of the factors causing fires in peatlands is due to the condition of dry peat. This condition can be caused by uncontrolled human activities such as digging canals that can lead a significant decreasing change of groundwater level in peatlands and cause peat to become dry. The Government of Indonesia, through BRG, is attempting to Rewetting the peatland by canal blocking. How effective the impact of canal blocking is analyzed in this study. To analyze the fluctuation of groundwater level as impact of canal blocking changes before and after canal blocking using water level loggers. Groundwater level monitoring was carried out on 3 transects, namely, 1 transect in the downstream side which is 100 m from the canalblock and 2 transects in the upstream side which is 114 m and 491 m from the canal block. The results showed that the canalblock had a good impact for keeping groundwater elevation and keeping peatland on always wet condition until 419 m with an increase of 0,005 m to the upstream area from canalblock and around 240 m with an increase of 0,005 m perpendicular to the canal.Key words: peatland, canal blocking, Rewetting